An Autopsy Study of Drowning Deaths in and around Visakhapatnam - Raja Sekhar Uppu1, BVS Ananda Rao2, Beemsetty Rajesh3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: According to World Health Organisation, drowning is among the ten leading causes of death for children and young people in every region of the world. Drowning amounts to an estimated incidence of about 5.6 per 100,000 of population worldwide. This study is aimed to know the incidence, manner and epidemiology of deaths due to drowning in and around Visakhapatnam.Materials and Method: It is a one year prospective post-mortem study of drowning in and around Visakhapatnam. All the deaths due to drowning that were autopsied at the mortuary, KGH, Visakhapatnam were studied based on inquest, post mortem examination findings to know the profile of drowning deaths.Results and Conclusion: Out of 1675 total autopsies done at our centre during the study period, 79 bodies that are found in water are studied. Males in the age group of 21-30 are the most common victims. Sea water drowning amounted for most cases of drowning in contrary to other studies. About 58% of cases of drowning were during the day. Most number of drowning deaths occurred in the month of October and monsoon season. Accidental drowning is the most common manner of death in males and suicidal manner in female drowning victims. About 32% of drowning victims in the study are from low socio-economic status. Most of the female victims are married while male victims are unmarried.